Prenatal health care beyond the obstetrics service: utilization and predictors of unscheduled care. - Magriples, Urania; Kershaw, Trace S; Rising, Sharon Schindler; Massey, Zohar; Ickovics, Jeannette R (American journal of obstetrics and gynecology, 2008)
The objective of the study was to describe the patient characteristics of prenatal care utilization within and outside of routine obstetric care, and the clinical and psychosocial factors that predict care utilization.
Keywords: Adolescent; Adult; Ambulatory Care Facilities; Appointments and Schedules; Female; Gestational Age; Health Care Surveys; Health Knowledge, Attitudes, Practice; Hospitals, University; Humans; Maternal Health Services; Multivariate Analysis; Obstetrics; Office Visits; Predictive Value of Tests; Pregnancy; Prenatal Care; Probability; Prospective Studies; Regression Analysis; Risk Assessment; Socioeconomic Factors